Human capital and global business strategy - Thomas, Howard 1943-; Smith, Richard R. 1962-; Diez, Fermin (Cambridge Univ. Press, 2013)
"Human capital - the performance and the potential of people in an organization - has become an increasingly urgent issue for business leaders. Dramatic demographic shifts, the globalization of organizations, increasing business complexity and generational differences are causing many organizations to take a more deliberate focus on human capital as a key element in strategic planning and execution. This book helps business leaders and HR professionals determine how to address human capital as part of their business strategy, to drive value and realize the potential of the organization. Topics are presented clearly, allowing readers to quickly grasp and apply key concepts and ideas. The authors share both their academic research and practical experience from around the world, providing case studies and examples to help bring theoretical topics to life. With a strong practitioner focus, this book will provide new insights into how to improve business performance through a unique, strategic approach to human capital"--